The theory of monopolistic competition : a re-orientation of the theory of value - Chamberlin, Edward Hastings (Cambridge, Mass. : Harvard University Press; London : Oxford University Press, 1956)
The study is divided into two main parts. In -the first, the author has analyzed imperfect competition where there are a few, but only a few, sellers of identical goods in the identical market-the problems of duopoly and oligopoly. The second and larger part of the book is an analysis of imperfect competition where the demands for the goods of different sellers are closely related but not identical. It is to the latter situations that the author more particularly applies the term "monopolistic competition ", and it is to the analysis of such situations "that special interest and importance attaches "The theory of monopolistic competition is concerned " not only with the problem of an individual equilibrium (the ordinary theory of monopoly), but also with that of a group equilibrium (the adjustment of economic forces within a group of competing monopolists, ordinarily regarded merely as a group of competitors)" (p. 69).
Includes index.
Includes bibliographical references: p. 277-346.
lje 14/06/2017
Loans
Keywords: Value; Competition; Monopolies; Prices; Economics, Mathematical